Illegitimate child in Malaysia - Wan Ahmad, Wan Ibrahim (American-Eurasian Network for Scientific Information (AENSI Publisher), 2013)
Until now little is known about the exact number of illegitimate child in Malaysia.Following the growing number of illegitimate child in Malaysia in recent years, research on illegitimate child has become the focus of extensive concern, and the discussion of illegitimate child has been considered necessary.Illegitimate child is related to problems such as inheritance, guardianship in marriage, the question of incest, and many others related to Islamic family law. The National Fatwa Council holds the opinion that only a child born after six months from the date of marriage can be considered legitimate.This paper discusses the main categories of illegitimate child according to Islamic law.Two informants related to lineage law in Malaysia have been interviewed.Data for this study are gathered through unstructured interviews.Results show that there are three categories of illegitimate child according to the Islamic law in Malaysia, namely a child born as a result of rape, a child born from pregnancy did not reach 6 months, as well as a child born from a pregnancy before marriage.